2020
DOI: 10.1111/andr.12907
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus: A possible cause of reduced male fertility

Abstract: In lately December 2019, a novel coronavirus (SARS‐CoV‐2) outbreak occurred in Wuhan, PR China. It is a high contagious virus that has threatened human health worldwide. SARS‐CoV‐2 infection, termed COVID‐19, causes rapidly developing lung lesions that can lead to multiple organ failure in a short period. Whenever a novel virus emerges, reproductive risk assessments should be performed after infection. In this review, we show that male fertility might be damaged by coronavirus associated with (i) direct cytopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 99 publications
(178 reference statements)
1
37
0
1
Order By: Relevance
“…17,23,24 Male patients with COVID-19 and high immunoglobulin G titre might also have adverse reproductive effects, possibly caused by anti-sperm antibodies such as antiphospholipid antibodies, which interfere with fertilisation. 25 Inflammatory infiltration may disrupt spermatogenesis, impede steroidogenesis, and destroy cells in seminiferous tubules. 26 Moreover, SAR-CoV-2 induces oxidative stress via inflammatory responses, which might disrupt the process of spermiogenesis and lead to spermatozoa having poorly remodelled chromatin.…”
Section: Orchitis In Coronavirus Infectionmentioning
confidence: 99%
“…17,23,24 Male patients with COVID-19 and high immunoglobulin G titre might also have adverse reproductive effects, possibly caused by anti-sperm antibodies such as antiphospholipid antibodies, which interfere with fertilisation. 25 Inflammatory infiltration may disrupt spermatogenesis, impede steroidogenesis, and destroy cells in seminiferous tubules. 26 Moreover, SAR-CoV-2 induces oxidative stress via inflammatory responses, which might disrupt the process of spermiogenesis and lead to spermatozoa having poorly remodelled chromatin.…”
Section: Orchitis In Coronavirus Infectionmentioning
confidence: 99%
“…This evidence leads to the hypothesis that semen could not be a route of SARSCoV-2 transmission and there is low risk of viral transmission through assisted reproductive techniques (ARTs) during COVID-19 outbreak. Eventually, severe destruction of the testicular tissue is quite evident in histopathological examinations despite the above finding ( 1 , 4 ).…”
mentioning
confidence: 95%
“…It has also been shown that high levels of IL-6 disrupt the integrity of BTB, which facilitates virus infiltration and probably direct damages to spermatogenic cells. In fact, this may be the reason for the various reports on orchitis-like syndrome in COVID-19 patients ( 1 , 5 ).…”
mentioning
confidence: 98%
See 2 more Smart Citations